Risk of malignancy in thyroid nodules selected for fine needle aspiration biopsy based on ultrasound risk stratification. (1st March 2022) - de Jong, Mechteld C; McNamara, John; McGlashan, Nicholas; Winter, Lucinda; Mihai, Radu
Abstract: Aim: Risk stratification of thyroid nodules based on ultrasound scan (USS) features using the TIRADS- or U-scale has been widely adopted. However, management decisions for patients whose work-up provide conflicting information, remains challenging. The aim of this study was to assess the rate of malignancy among those with suspicious cytology after USS-evaluation. Methods: Retrospective review of clinical, radiological and pathological data regarding patients presenting with a thyroid nodule. Results: Between January 2018 and December 2020, a total of 214 patients underwent surgery after presenting with thyroid nodule(s) and a fine-needle aspiration (FNA) cytology report either suspicious (Thy3–4) or diagnostic (Thy5) for thyroid malignancy. The appearance on USS was stratified using the TIRADS-scale, either to select nodules needing FNA-assessment or to characterise palpable nodules. For Thy3a-cytology, the risk of malignancy remained low, irrespective of USS-appearance (2/15 in TIRADS2-3 versus 2/9 in TIRADS 4-5). For a Thy3f-cytology, the risk of malignancy was higher if the USS-appearance was also suspicious (11/75 in TIRADS2-3 versus 17/69 in TIRADS 4-5, p =0.03). High-risk USS-appearance (TIRADS 4-5) in the presence of suspicious/diagnostic cytology (Thy4-5) had a 95% positive predictive value (40/42) of malignancy. Future data collection should assess the risk of malignancy when USS-appearance is malignant (TIRADS 5) yet cytology is benign (Thy2). Conclusion: The performance of USS and FNA in this cohort corroborates published data. Until genetic panels will complement the assessment of nodules with a Thy3-cytology, diagnostic thyroid lobectomy remains necessary, as the USS has limited ability to increase the yield of malignant nodules.